Mybanjir update system using mobile application - Muhammad Adib, Nor Azahar (2014)
Nowadays, the usage of mobile technology has become a trend in a huge area such as education, entertainment, online business and other kind of area that gives benefits. Mobile applications enable new ways of working in an increasingly connected and mobile world. Enterprises realize the advantages and are gearing up to get ahead. With the increasing numbers of mobile applications being deployed, it’s important for organizations to make the most efficient investments for their enterprise mobility needs. Mobile development platforms with multi-channel deployment capabilities, security, management and back-end integration capabilities make a whole lot of sense. Besides, mobile application allows fast and effective data management through the internetwork facilities. Data can be sent via wireless network from mobile device to the web server in a very fast connection. The MyBanjir Update System is the interactions between the web based servers communicate to mobile application. Flood information sometimes is not being announced in a suitable condition. The information usually spread in television and radio but when floods occurred, the electricity around the area is break down. This is the main problem for user to stay in touch with the flood reports. Using this MyBanjir Update Mobile Application helps them to get directs update using their smartphones together with the internet connection. The MyBanjir Update System for the web server is responsible for staff in Jabatan Meteorologi Pahang to pass the flood information to the user using the mobile application. The result of using this MyBanjir Update Mobile Application is much faster and can be used in anytime and anywhere as long as there is an internet connection.